The impacts of knowledge worker and skills in the industrial revolution 4.0: empirical evidence from selected Asean+3 countries / Noorazeela Zainol Abidin, Zainebbeevi Kamalbatcha and Nuraini Abdullah - Zainol Abidin, Noorazeela; Kamalbatcha, Zainebbeevi; Abdullah, Nuraini (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
The rapid pace of technological change presents significant challenges for academic institutions and professionals. The importance of knowledge workers and skills in enabling businesses to compete in the era of Industry 4.0 is paramount, reshaping the global economy. This study investigated the impacts of knowledge workers and skills on technology from 1990 to 2021. This study utilized pooled mean group (PMG), mean group (MG), and dynamic fixed effect (DFE) models from dynamic panel techniques. The Hausman test identified the PMG estimator as the most suitable for this research. PMG’s findings revealed a substantial, consistent impact of knowledge workers on R&D over time. Additionally, the gap between highly skilled and semi-skilled employees negatively affected R&D. In the short term, FDI exhibited a negative yet significant impact on R&D, while the interaction between high-skilled and nation-dummies positively influences R&D. Thus, policymakers should prioritize enhancing the educational system through new initiatives and support programs. Moreover, increased government funding and support for employer-led training programs are essential to meet the rising demand for skilled workers. Businesses must also foster employee skill development to thrive in the impending industrial revolution.